Using computer simulations to compare pertussis vaccination strategies in Australia. - Hethcote, H; Horby, P; McIntyre, P (2004)
High levels of notified pertussis in adolescents and adults, persisting severe disease (hospitalization and deaths) in infants despite high childhood immunization coverage, together with the availability of adult-formulated pertussis vaccines, have made alternate strategies for vaccine control of pertussis an important issue in Australia. An age-structured computer simulation model was used to compare the likely effects of adopting different vaccination strategies in Australia on pertussis transmission by age group over a 50 year time period. Epidemiological parameters and vaccination coverage in Australia were estimated from previous pertussis modeling studies and existing data. In the simulations, replacing the pertussis booster at 18 months with a booster dose for adolescents at an age between 12 and 17 years, assuming 80% coverage, led to decreases in pertussis cases of 30% in children of ages 0-23 months (who have the highest complication rates) and of 25% in adolescents, but an increase of 15% in cases in 2-4-year-old children. The simulations did not suggest any shift of pertussis cases into the adult child-bearing years. Varying parameter values in the simulations in a series of sensitivity analyses showed the model predictions to be robust over a plausible range. The results of these simulations suggest that the recent change in the Australian pertussis vaccination schedule, replacing the 18 month dose with a pertussis booster in 15-17-year-old adolescents, is very likely to reduce overall pertussis incidence in Australia without increasing the cost of the current vaccine program.